'Alliance with the Enemy': Why the CDU and the Greens Formed Their First Coalition in a Large German Federal State. Issue 1 (2nd January 2016) - Steinert, Christoph; Yordanova, Nikoleta
Abstract : This article seeks to explain the 2013 coalition between the CDU and the Greens in the German federal state of Hesse. It applies traditional office-seeking and policy-seeking coalition formation theories to the case alongside a new explanation underscoring the influence of past behaviour on coalition partnership; namely, the negative impact of a pre-electoral commitment breach on future coalition formation. The results show that pure office-seeking cannot explain the coalition outcome. Instead, as the analysis of textual data extracted from political parties' manifestos shows, there has been a constant process of policy approximation between the CDU and the Greens in Hesse. Additionally, we find evidence suggesting that the SPD's breach on their promise not to rely on support by the Left Party in 2008 shaped the CDU's refusal to coalesce with the SPD in 2013. The findings add to our understanding of the interplay between office-seeking and policy-seeking motivations as well as the personal enmities of key actors in shaping the coalition formation. The study further offers insights into the new German coalition option between the Greens and the CDU, which can serve as a blueprint at the national level.